Cover Picture: An Ultrastable, Small {Ag7}5+ Nanocluster within a Triangular Hollow Polyoxometalate Framework (Angew. Chem. Int. Ed. 38/2020). Issue 38 (4th August 2020) - Yonesato, Kentaro; Ito, Hiroyasu; Yokogawa, Daisuke; Yamaguchi, Kazuya; Suzuki, Kosuke
Abstract : An ultrastable silver nanocluster was synthesized by K. Yamaguchi, K. Suzuki et al. in their Communication on page 16361 by using lacunary polyoxometalates. In the cover picture, the green polyhedra represent lacunary polyoxometalates and the light gray spheres silver atoms. While small silver nanoclusters are typically highly fragile, the small Ag7 nanocluster shows unprecedented stability when surrounded by a triangular hollow polyoxometalate framework.